Numerals Expressing Abundance in Lithuanian, Hindi and Urdu Languages - Ranjan, Rasa (Acta Orientalia Vilnensia, 2003)
The object of research in this article is the names of numerals expressing abundance in the three Indo-European languages - Lithuanian, Hindi and Urdu - which are very far from one another in the genetic, cultural, historical, geographical and religious perspective. The contrastive-descriptive method is applied to the analysis of the phraseological compounds, proverbs and sayings of the languages mentioned above, where the conception of abundance, plenitude and infinity is outlined by numerals. Especially big attention is paid to the analysis of the associations evoked by the name of one or another number making use of the psychological and logical-semantic contrastive criteria. The influence of counting systems, religious symbolism (Catholicism, Hinduism and Islam), and true-life experience on the nature of metaphorical meanings is being discussed.